Energy crime, harm, and problematic sate response in Colorado: a case of the fox guarding the hen house? - Opsal, Tara (Critical criminology, 2014)
Crime related to energy extraction is an emerging area of interest among green and critical criminologists. This paper contributes to that developing work by examining the political economy of harm and crime associated with the oil and natural gas industry in rural Colorado. Specifically, we examine problematic state regulatory response to citizens’ complaints regarding a range of harms caused by private industry (e.g., water pollution, adverse human health consequences, and domestic livestock death). In this paper, we draw on content analysis of formal complaints filed by citizens to the state, ethnographic work, and intensive interviews with citizens seeking relief from problematic or abusive industry practices. Our analysis illuminates how the state documents these practices, how citizens experience them, and how the state dilutes and deflects the externalities of energy extraction to produce additional harm.